Evaluating the potential for tactical hunting in the Middle Stone Age: Insights from a bonebed of the extinct bovid, Rusingoryx atopocranion. Issue 108 (July 2017) - Jenkins, Kirsten E.; Nightingale, Sheila; Faith, J. Tyler; Peppe, Daniel J.; Michel, Lauren A.; Driese, Steven G.; McNulty, Kieran P.; Tryon, Christian A.
Abstract: The foraging behaviors of Middle Stone Age (MSA) early modern humans have largely been based on evidence from well-stratified cave sites in South Africa. Whereas these sites have provided an abundance of data for behavioral reconstruction that are unmatched elsewhere in Africa, they are unlikely to preserve evidence of the diversity of foraging strategies employed by MSA hunters who lived in a variety of ecological and landscape settings across the African continent. Here we describe the results of recent excavations at the open-air site of Bovid Hill at Wakondo, Rusinga Island, Kenya, which yielded 24 in situ MSA artifacts within an assemblage of bones comprised exclusively of the extinct alcelaphin bovid Rusingoryx atopocranion. The excavated faunal assemblage is characterized by a prime-age-dominated mortality profile and includes cut-marked specimens and an associated MSA Levallois blade-based artifact industry recovered from a channel deposit dated to 68 ± 5 ka by optically stimulated luminescence. Taphonomic, geologic, and faunal evidence points to mass exploitation of Rusingoryx by humans at Bovid Hill, which likely represents an initial processing site that was altered post-depositionally by fluvial processes. This site highlights the importance of rivers and streams for mass procurement in an open and seasonal landscape, and provides important new insights into MSA behavioral variability with respect to environmental conditions, site function, and tactical foraging strategies in eastern Africa. Bovid Hill thus joins a growing number of MSA and Middle Paleolithic localities that are suggestive of tactical hunting behaviors and mass capture of gregarious ungulate prey.